Integrated Waste Management : Volume I - Kumar, Sunil; Kumar, Sunil (IntechOpen, 2011)
This book reports research on policy and legal issues, anaerobic digestion of solid waste under processing aspects, industrial waste, application of GIS and LCA in waste management, and a couple of research papers relating to leachate and odour management.
English
Keywords: Urban & municipal planning; Urban & municipal planning